Generation and Immune Regulation of CD4+CD25−Foxp3+ T Cells in Chronic Obstructive Pulmonary Disease - Wu, Jiang-Hua; Zhou, Mei; Jin, Yang; Meng, Zhao-Ji; Xiong, Xian-Zhi; Sun, Sheng-Wen; Miao, Shuai-Ying; Han, Hong-Li; Tao, Xiao-Nan (Frontiers in Immunology, 2019)
The imbalance of CD4+Foxp3+ T cell subsets is reportedly involved in abnormal inflammatory immune responses in patients with chronic obstructive pulmonary disease (COPD). However, the possible role of CD4+CD25−Foxp3+ T cells in immune regulation in COPD remains to be investigated. In the current study, distribution and phenotypic characteristics of CD4+CD25−Foxp3+ T cells from peripheral blood were determined by flow cytometry; the origin, immune function and ultimate fate of CD4+CD25−Foxp3+ T cells were further explored in vitro. It was observed that circulating CD4+CD25−Foxp3+ T cells were significantly increased in stable COPD patients (SCOPD) and resembled central memory or effector memory T cells. Compared with peripheral CD4+CD25+Foxp3+ T cells, peripheral CD4+CD25−Foxp3+ T cells showed a lower expression of Foxp3, CTLA-4, HELIOS and TIGIT, but a higher expression of CD127 and KI-67, suggesting that CD4+CD25−Foxp3+ T cells lost the expression of Tregs-associated molecules following the reduction in CD25. Unexpectedly, our study found that transforming growth factor-β1 (TGFβ1) decreased CD25 expression and played a critical role in the generation of CD4+CD25−Foxp3+ T cells from CD4+CD25+Foxp3+ T cells. Phenotypic analysis further revealed that both inducible and peripheral CD4+CD25−Foxp3+ T cells exhibit the features of activated conventional T cells. Importantly, memory CD4+CD25−Foxp3+ T cells facilitated the proliferation and differentiation of naïve CD4+ T cells into Th17 cells in the presence of IL-1β, IL-6, IL-23 and TGFβ1. Finally, a fraction of CD4+CD25−Foxp3+ T cells, exhibiting instability and plasticity, were converted to Th17 cells when subjected to Th17 cell-polarizing condition. Taken together, we propose that TGFβ1 is responsible for the generation of CD4+CD25−Foxp3+ T cells, which functionally exert an auxiliary effect on Th17 cells generation and might perpetuate chronic inflammation in COPD.